2019
DOI: 10.3390/nu11010175
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast Choice Is Associated with Nutrient, Food Group and Discretionary Intakes in Australian Adults at Both Breakfast and the Rest of the Day

Abstract: Breakfast choice is correlated with daily nutrient intakes, but this association may not be solely explained by the breakfast meal. We profiled breakfast consumer groups among Australian adults and compared the role that breakfast versus the rest of the day had on daily intakes of the Five Food Groups, discretionary foods, and nutrients. Breakfast groups were breakfast cereal consumers, non-cereal breakfast consumers, and breakfast skippers. One-day dietary recall data from the 2011–2012 National Nutrition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 57 publications
3
36
0
Order By: Relevance
“…Breakfast consumption was associated with an older age whereas breakfast skipping (5.5% of sample) was found to be highest among adolescents. This finding is consistent with a body of evidence from several countries [ 6 , 7 , 8 , 10 , 11 , 39 ] showing that regularity of breakfast intake is commonly lower in adolescents compared to adults of the same populations. Although some studies have hypothesized that this age difference could be a transient phenomenon from a lower frequency of breakfast in adolescents to a regular consumption in adulthood [ 6 ], this does not seem to be the case for part of the LA countries assessed in ELANS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Breakfast consumption was associated with an older age whereas breakfast skipping (5.5% of sample) was found to be highest among adolescents. This finding is consistent with a body of evidence from several countries [ 6 , 7 , 8 , 10 , 11 , 39 ] showing that regularity of breakfast intake is commonly lower in adolescents compared to adults of the same populations. Although some studies have hypothesized that this age difference could be a transient phenomenon from a lower frequency of breakfast in adolescents to a regular consumption in adulthood [ 6 ], this does not seem to be the case for part of the LA countries assessed in ELANS.…”
Section: Discussionsupporting
confidence: 92%
“…Argentina was the only country which has exceeded the recommendations for total carbohydrates in this meal [ 50 ] and this has been explained by the intake of added sugar 2.5 times higher than recommended [ 51 ]. Of note, all countries presented an added sugar intake above the recommendation of 10% [ 51 ], which corroborates with previous findings from other IBRI studies [ 6 , 7 , 8 , 11 , 39 ] and from ELANS [ 52 , 53 ].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, participants who eat breakfast after one hour of waking up eat less fruits and more fat-rich grains. Similarly to our results, Australian adults who skip breakfast were less likely to eat grain foods, fruits, and vegetables; and were more likely to eat refined foods, compared to breakfast consumers [33]. Also, breakfast skippers had the highest intake of added and free sugars, and the lowest micronutrient intake [34].…”
Section: Discussionsupporting
confidence: 80%
“…Another possible explanation for the seemingly protective effect of breakfast on body weight is that breakfast consumers display other health‐related behaviors. A 2019 Australian observational study found that differences in daily diet intake among cereal breakfast eaters, noncereal breakfast eaters, and breakfast skippers were attributable to different food choices both at breakfast and during the rest of the day (32). Furthermore, in a 10‐year prospective study, the protective effect of breakfast consumption on the prevention of weight gain was partially explained by fiber and nutrient intake (6).…”
Section: Discussionmentioning
confidence: 99%